The Analysis of Politeness Strategies in Jimmy O. Yang: Good Deal (2020) - Fathir Faza Herryanto; Sri Fajar Nurrohim, (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2025)
This study analyzes the use of politeness strategies in stand-up comedy performance titled Jimmy O. Yang: Good Deal (2020), focusing on Jimmy O. Yang who delivers humor with implied meaning through a pragmatic lens. This research aims to identify the types of the politeness strategies used by Jimmy O. Yang and to analyze the functions of each politeness strategy. This research applies Brown and Levinson’s (1987) theory of politeness as the main theory to identify the types of politeness strategies and to analyze the function of each strategy. It employs a qualitative descriptive method by Creswell & Creswell (2018) to analyze the data. This study uses document analysis as the data collection method, as proposed by Creswell & Creswell (2018). It involved watching the show, analyzing the transcript, and recording instances of humor with implied meanings. The findings show three politeness strategies found in Yang’s performance, with off record strategies as the most dominant. Positive politeness is used to build audience rapport, and bald on record strategies appear in low-risk, functional moments